2017
DOI: 10.1093/jac/dkx220
|View full text |Cite
|
Sign up to set email alerts
|

Has primary care antimicrobial use really been increasing? Comparison of changes in different prescribing measures for a complete geographic population 1995–2014

Abstract: Rising antimicrobial volumes up to 2011 were mainly due to rising DDD per prescription. Trends in dispensed drug volumes do not readily translate into information on individual exposure, which is more relevant for adverse consequences including emergence of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…The trends in total antibiotic utilisation reported here are consistent with national trends based on aggregate data 2. Neilly et al 26 found that increasing prescription volumes in the period up to 2013 could be accounted for by increasing dose and duration of prescriptions but we found evidence of increased antibiotic prescribing based on numbers of prescriptions alone. Consistent with our findings, Balinskaite et al 11 reported increasing rates of infection in English primary care and hospital admissions data from 2010 to 2017.…”
Section: Discussioncontrasting
confidence: 70%
“…The trends in total antibiotic utilisation reported here are consistent with national trends based on aggregate data 2. Neilly et al 26 found that increasing prescription volumes in the period up to 2013 could be accounted for by increasing dose and duration of prescriptions but we found evidence of increased antibiotic prescribing based on numbers of prescriptions alone. Consistent with our findings, Balinskaite et al 11 reported increasing rates of infection in English primary care and hospital admissions data from 2010 to 2017.…”
Section: Discussioncontrasting
confidence: 70%
“…Strong improvements have also been observed in other European countries, including the Italian Region Emilia Romagna, the Netherlands, Scotland and Sweden. In Scotland, the antibiotic prescription rate in children younger than 5 years decreased by 60% from 1,612 to 634 per 1,000 persons between 1995 and 2014 [ 14 ]. In the Netherlands, antibiotic use among 0–14 year-olds, measured as packages per population, decreased by 8–17% depending on age between 2012 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the prescription rate is a good approximation for the rate of antibiotic treatments at population level. In addition, prescription rates are robust towards alterations of dosage per prescription over time, which may arise from changes in the prescribing practice for specific drugs or changes in the mix of antibiotics used [ 14 ]. To capture possible changes in dosage per prescription over time, mean annual DDD per prescription were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…However, total antimicrobial consumption expressed in DDDs/ 1000 residents-days should be interpreted carefully as it may not accurately reflect antimicrobial use. Neilly et al found an increase in antimicrobial DDDs in contrast to a decrease in the mean number of prescriptions over the study period [54]. In addition, the DDD method inaccurately estimated days of therapy when the actual daily dose was not equal to the DDD, and this method was not recommended in situations where reduced doses were advocated e.g.…”
Section: Discussionmentioning
confidence: 99%